Gene flow in Dubautia arborea and D. ciliolata: the roles of ecology and isolation by distance in maintaining species boundaries despite ongoing hybridization - FRIAR, E.A; CRUSE-SANDERS, J.M; McGLAUGHLIN, M.E (Molecular ecology, 2007)
The relative roles of gene flow and natural selection in maintaining species differentiation have been a subject of debate for some time. The traditional view is that gene flow constrains adaptive divergence and maintains species cohesiveness. Alternatively, ecological speciation posits that the reverse is true: that adaptive ecological differentiation constrains gene flow. In this study, we examine gene flow and population differentiation among populations of two species of the Hawaiian silversword alliance, Dubautia arborea and D. ciliolata. We compare divergence in putatively neutral microsatellite markers with divergence in leaf morphometric traits, which may be selectively important or physiologically linked to selectively important traits. Gene flow between populations was found to be significant in only one of the two species, D. arborea. Leaf morphometric differentiation between species was significant, though not among populations within species. No evidence of effective genetic introgression was observed between apparently 'pure' populations of these species. Gene flow as measured by microsatellites was not correlated with geographic distance between populations, but was correlated with the linear placement of the widest part of the leaf. Because these two species are interfertile, as demonstrated by the presence of active hybrid zone, the lack of genetic introgression and the maintenance of species boundaries may be associated with natural selection on differential habitat.